Ignition probability of fine dead surface fuels in native Patagoniaforests of Argentina - Bianchi, Lucas Osvaldo (2013)
Fil: Bianchi, Lucas O. Centro de Investigación y Extensión Forestal Andino Patagónico; Argentina.